Implementation of the Wafa Method in Learning Quran Tahfizh - Amelya, Amelya; Eramahi, Eka; Oktavia, Gifa (STIT Ahlussunnah Bukittinggi, 2023)
This research aims to determine the implementation of the Wafa method in learning tahfizh Quran, to determine the evaluation of the Wafa method in learning tahfizh Quran and to determine the supporting and inhibiting factors of the Wafa method in learning tahfizh Quran at the Tahfizh School of Light Above Light. This research uses a descriptive qualitative approach. Data collection techniques: observation, interviews, and documentation with data analysis through data reduction, data presentation, and drawing conclusions and verification. The results of this research analysis show that the implementation of the Wafa method in learning tahfzih Quran at Tahfizh Cahaya di Atas Cahaya School is as follows: Preparations made by teachers in learning tahfizh Quran, namely teachers plan learning by making learning tools such as learning process plan, Wafa book as a learning medium and the Quran as the main source. Implementation of learning means the teacher instills intention and motivates students before learning begins. Evaluation of students' abilities is carried out by the teacher by testing the memorization of the Quran which has previously been memorized. Supporting factors are adequate infrastructure, and a conducive school environment, while inhibiting factors are teachers' uneven understanding of the Wafa method, the existence of children's different learning styles, and a lack of cooperation between teachers and parents. The results of this research can provide guidance for the Tahfizh Cahaya di Atas Cahaya School and perhaps also for other schools, and can be used as initial data for future researchers in studying this problem in different contexts and issues.